Hydrometallurgic treatment of gold disseminated in pyrite and arsenopyrite from flotation tailing - Azañero Ortiz, Angel (2010)
Tailings come from a mineral containing copper, silver and gold and recovery percentages of 90% of copper, 55 % of silver and 10% of gold from flotation. The study and mineralogic characteristic made to tail at 200 x magnification shows the presence of 54% of pyrite and 43% of gangue, does not detect gold, and has a chemical analysis of 3.74 gr/TM gold and 4.18 Oz/TC silver. The cyanidation tests made to the reground tailings at – 45 u give poor recoveries, 10% at most, reinforcing the hypothesis that the precious metal is in solid solution in the pyrite. Based on these results, cyanide lixiviation tests are performed using air and pyrometallurgical oxidation, in the first case 40% of cyanide dissolution is obtained trough air oxidation in alkaline media, and in the second case, 90% of gold is recovered trough roasting tests at 600° C, calcine wash to diminish the consumption of reactives followed by cyanidation by agitation.